2019
DOI: 10.1063/1.5099352
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Rashba spin splitting in 2D organic-inorganic perovskite via precessional carrier spin relaxation

Abstract: The strong spin-orbit interaction in the organic-inorganic perovskites tied to the incorporation of heavy elements (e.g. Pb, I) makes these materials interesting for applications in spintronics. Due to a lack of inversion symmetry associated with distortions of the metal-halide octahedra, the Rashba effect (used e.g. in spin field-effect transistors and spin filters) has been predicted to be much larger in these materials than in traditional III-V semiconductors such as GaAs, supported by the recent observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 78 publications
5
64
1
Order By: Relevance
“…While the CsPbBr 3 crystal structure is centrosymmetric, local thermal fluctuation can create dynamic symmetry breaking and Rashba effect (5,43). The Rashba effect has also been invoked in discussing the spin depolarization process in perovskites (34,45). In principle, both the polaronic effect and the Rashba effect can retard electronhole recombination, but differentiating their relative contribution has been a longstanding challenge.…”
Section: Resultsmentioning
confidence: 99%
“…While the CsPbBr 3 crystal structure is centrosymmetric, local thermal fluctuation can create dynamic symmetry breaking and Rashba effect (5,43). The Rashba effect has also been invoked in discussing the spin depolarization process in perovskites (34,45). In principle, both the polaronic effect and the Rashba effect can retard electronhole recombination, but differentiating their relative contribution has been a longstanding challenge.…”
Section: Resultsmentioning
confidence: 99%
“…[ 191,192 ] Due to the presence of Pb, it is reported that lead‐halide perovskites in both 3D and 2D forms possess giant Rashba coupling, thus outperforming many other semiconductors. [ 193,194 ] As a consequence of the Rashba coupling, the defect‐induced recombination is substantially suppressed, which grants halide perovskites with high defect tolerance. Based on these desirable features, an ultra‐long carrier diffusion length >175 µm has been reported in MAPbI 3 single crystals.…”
Section: Perovskite‐based Transistorsmentioning
confidence: 99%
“…Even with field induced Rashba splitting, the spins can still continuously transform in the ground states, so the optical helicity also exhibits very short lifetime. [ 39 ] The discrete K/K′ valleys in Cs 3 Bi 2 I 9 are important for memory devices.…”
Section: Figurementioning
confidence: 99%